Pemeriksaan Golongan Darah dan Rhesus Pelajar Kelas 5 dan 6 Sekolah Dasar di Desa Taro Kecataman Tegallalang Gianyar - Swastini, D.A.; Lestari, A. A.W.; Laksmiani, N.P.L.; Setyawan, E.I. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
Examination of blood type has many benefits and shorten the identification time, in the interests of transfusion , right blood donor, and the identification in forensic cases such as the identification of criminal cases, in the other hand, blood type and rhesus checks also one of the prerequisites to attend junior high school from elementary school. Academic data of year 2014/2015 shows, none of the children in elementary school at Taro village, ever checked blood type or rhesus, so it is necessary to do this activity especially for 5 and 6 grade of students at elementary school. Examination includes blood type systems A, B , O and Rh. This examination followed by 139 students in grade 5 and 6 from SDN 1 , 2 , 3 , 4 of Taro, with the distribution age of the participants between 11 to 16 years. The test results showed 18.71 % of the participants have A blood type , 41.01 % with B blood type , 5.04 % AB blood type and 35.25 % with O blood type. All participants have a positive Rhesus ( Rh + ).
Keywords: blood type , ABO, rhesus, elementary school, Taro village